Kebebasan Manusia dalam Berkehendak dan Berbuat: Analisis Persoalan Klasik dalam Konteks Kehidupan Berbangsa di Indonesia - Muhammad Agung Raharjo; Andi Aderus; Hamzah Harun (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
This study aims to analyze human freedom to will and act based on philosophical, theological, and practical views, and explore its application in national life in Indonesia. The main focus of this study is to find thoughts that can lead the Indonesian nation to progress, be respected, and continue to receive the grace of Allah SWT. The method used in this study is a literature review with a descriptive-analytical approach, in which various expert views, theories, and concepts about freedom are analyzed and adjusted to the context of social, political, and economic life in Indonesia. The results of the study show that human freedom to will and act must be integrated with the values ​​of Pancasila and theological principles of Islam, such as ikhtiar and destiny, to create responsible freedom. In addition, freedom of opinion needs to be managed wisely in order to strengthen democracy and maintain socio-political stability. In the economic sector, freedom must be combined with policies based on social justice to reduce inequality and create inclusive growth. This study also highlights the importance of responsible freedom thinking, as offered by Nurcholish Madjid, to encourage national progress that remains based on spiritual values. The results of this discussion show that human freedom in various aspects of life can be the foundation for the progress of the nation, as long as it is managed with the values ​​of responsibility and spirituality. With this approach, Indonesia can become a nation that is advanced, competitive, and full of blessings.